Perencanaan Humas dan Usaha Membangun Citra Lembaga yang Unggul - Mulyadi, Slamet (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Public relations, commonly called public relations, are key players in the relationship between educational institutions and the public or the public. Because he is a communication link between the two. Public relation has been spread in various agencies both the government and its parts (police, meliter, and so on), organizations, boarding schools, foundations, educational institutions and others. but whether it is already running as the public relations in management know just the name. In the discussion of the task of these public relations planning models the author uses argumentative descriptive methods. That is describing public relations planning models with reviews that can be accounted for. Supported by several studies in published journals on public relations planning model, this journal presents findings that can help in developing educational institutions hususnnya part of public relations. From this descriptive method of argumentative research, the problem encountered is that most educational institutions do not function public relations as management. public relations are only complementary and there are only important subjects. therefore the offer from this article how public relations or public relations provides an overview of how public relations are functioned and executed. As a liaison anntara within its own internal institutions and institutions with the public. public relations acts as a synergistic part, between institutions and the public both benefit or take and give. Hopefully useful, amen. Key Word : Planning, Public Relations, Institutional Image